Encoding and retrieval biases for health-related scenes in patients with severe health anxiety*. Issue 8 (14th September 2019) - Gehrt, Tine B.; Niziurski, Julie A.; Frostholm, Lisbeth; Berntsen, Dorthe
ABSTRACT: Severe health anxiety is a disorder characterised by excessive worries about harbouring or having a serious illness. The present study examines cognitive biases in evaluation and memory for health-related scenes in severe health anxiety in order to provide insights into the effect of these biases and the formation of illness intrusions in severe health anxiety. Twenty patients with severe health anxiety and 20 healthy participants completed a computerised task consisting of encoding, involuntary retrieval, voluntary retrieval and recognition of health-related, negative and neutral scenes. The results demonstrated that patients with severe health anxiety reported more negative emotional valence and greater physiological arousal to health-related scenes, both during encoding ( p s < .031, η p 2  > .09) and retrieval ( p s < .044, d s > 0.18). Furthermore, in contrast to the comparison group, patients with severe health anxiety did not show shorter retrieval time for health-related scenes during involuntary compared with voluntary retrieval ( p  = .789, d  = 0.08), possibly due to greater demands on emotion regulation during involuntary retrieval. The results suggest an important role for negative emotional valence and physiological arousal to health-related stimuli in severe health anxiety, and highlight how cognitive biases in evaluation and memory might be at play in this disorder.